The Relevance of Ontology in Educational Management from the Perspective of Islamic Educational Philosophy - Budianto; Syukri SS, Ahmad; Badarussyamsi (International Journal of Education, Language, and Social Science, 2024)
Islamic education management as a discipline has complex and profound dimensions, one of which is in the study of ontology which discusses the nature of reality and existence in the context of Islamic education. This article aims to analyze the theory of Islamic education management science through an ontological perspective by referring to the thoughts of a number of Muslim experts, such as Syed Muhammad Naquib al-Attas and Imam al-Ghazali. This ontological approach focuses on the nature of humans, the purpose of education, and how Islamic education management is structured in accordance with Islamic values. Using the literature review method, this article presents basic concepts in Islamic education and their relevance to education management. The results of the study show that ontology in Islamic education emphasizes the balance between spiritual and material dimensions, as well as the importance of integrating knowledge and morals in every aspect of education. This article is expected to provide new insights into the management of Islamic education that is more comprehensive and based on solid Islamic values.